Effects of Teacher Education Programs on Instructional Design Knowledge with Student Teachers’ Self-efficacy Perception and TPACK Framework Knowledge - Kaitbanditkul, Nuttaporn; Wongwanich, Suwimon (Thammasat Review, 2016)
This research has two main objectives. Firstly, to develop a causal model of teacher-education programs affecting the instructional design knowledge (and verification of the selected model for fitness for purpose). Secondly, to analyze the nature of direct effect on the mediation of teacher-education programs on instructional design knowledge, as well as the indirect effect mediation of TPACK framework knowledge with self-efficacy perception in the design of teaching programs. The samples consisted of 517 fifth-year student-teachers from universities within the Bangkok catchment area, drawn from a random sampling. The questionnaire for the design of teaching programs became the research instrument and the data were analyzed by Descriptive Statistics, Structural Equation Modeling Analysis (using LISREL Program). The findings included the following: 1) the model was appropriate for empirical data with Chi-Square value distribution (χ2 = 5.44; df = 8; p-value = .709) (which was statistically insignificant). Goodness-of-Fit Index (GFI) value was .997 and the Adjusted Goodness-of-Fit Index (AGFI) value was .988, indicating that the model was consistent with empirical data; 2) Causal Model of teacher-training programs affecting the design of instructional knowledge is the partial mediating research model. The design of instructional knowledge benefited directly from the experience gained through teacher-training programs (.34) and indirectly through the involvement of self-efficacy perception and TPACK framework knowledge (.54). All values are at .05 statistical significance level.